Clinical Feature of Langerhans Cell Histiocytosis of the Orbit : A First Case Series in Indonesia: Poster Presentation - Case Series - Ophthalmologist - ZENDY SAGITA; NENI ANGGRAINI; MUTMAINAH (Majalah Oftalmologi Indonesia, 2023)
Introduction : Langer hans histiocytosis (LCH) is an inexplicable disease characterized by proliferation of Langerhans and intermixed with inflammatory cell, in particular eosinophil, which represents only 1% pediatric orbital tumours. Orbital involvement of LCH is a rare clinical entity as the disease simulate variety of malignancies and present as a diagnostic and management dilemma for ophthalmologist. Case Illustration : Two cases of toddler presented with unilateral progressive upper eyelid swelling and proptosis for more than a month. Both cases has history of orbital trauma 1 month before swelling was observed. Initial CT scan revealed extraconal mass, with destruction of lateral orbital wall and frontal bone. Both patients had histopathological biopsy confirmed eosinophlic cytoplasm. One patient confirmed immunohistochemistry markers S100 and CD1a which is specific for Langerhans cells. Both patients continue with chemotherapy as definitive treatment. Discussion : LCH is a wide clinical spectrum which manifestation simulate other pediatric orbital malignancies. Case illustration present unilateral eyelid swelling with history of trauma may resemble other diagnosis unless further work up is performed. This case series exhibits clinical manifestations that may be suggestive of LCH. Considering rapid progression of disease, definitive diagnosis is a mandatory based on histopatological analysis through biopsy surgery. Conclusion : LCH is rare disease, it should be considered as one of deferential diagnosis in pediatric orbital malignancy with initial presentation acute unilateral eyelid swelling, proptosis, history of trauma, extraconal mass and destruction of bones as radiological features. This might be helpful for early recognition and prompt treatment of disease suggestive of LCH.